PENGARUH SERVICE EXCELLENCE TERHADAP LOYALITAS PELANGGAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) DI BATURAJA - Fitri Yanti; Yuniarti Anwar; Sally Maria Bramana (STIE DWI SAKTI BATURAJA, 2022)
This study aims to how much influence service excellence has on customer loyalty at regional drinking water companies (PDAM) in Baturaja. The research method used is descriptive method using qualitative and quantitative analysis. Data collection techniques used are observation, interviews, questionnaires, documentation and literature study. The population in this study are customers at regional drinking water companies (PDAMs) in Baturaja, in 2021 totaling 17,000 customers using non-probability sampling technique. The sample in this study amounted to 99 respondents. Based on the results of data analysis that has been carried out with the results of simple linear regression Y = 5,100 + 0,796 X. The results of the correlation coefficient analysis are 0,843. From this value, it can be interpreted that the relationship between service excellence (X) and customer loyalty (Y) is very strong. The result of the analysis of the coefficient of determination (R2) or R Square is 0.710 or 71%. This shows that customer loyalty (Y) is influenced by 71% by service excellence (X), while the remaining 29% is influenced by other variables not examined in this study. Hypothesis testing (t test) was carried out to determine whether there was a significant effect between the service excellence variable (X) on the customer loyalty variable (Y), it is known that the tcount value is higher than the ttable value, namely 15,415 > 1,984 meaning Ho is rejected and Ha is accepted, meaning that there is an influence. service excellence has a significant impact on customer loyalty to regional drinking water companies (PDAMs) in Baturaja.